The impact of security and its antecedents in behaviour intention of using e-government services. Issue 6 (3rd June 2017) - Alharbi, Nawaf; Papadaki, Maria; Dowland, Paul
ABSTRACT: One of the main challenges associated with e-government adoption is lack of security. Thus, the aim of this research is to investigate the role of security in e-government adoption by integrating security, trust and privacy with the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). In addition, this research will also investigate the factors that influence the end users' perception of e-government security. Thus, the research starts with a qualitative study to investigate security antecedents, and this is followed by a quantitative study to validate the qualitative study and determine the role of security in e-government adoption. Data from 625 Saudi citizens were gathered and used in the model assessment. The findings show that user interface quality, security culture and cybersecurity law positively affect security perception. In addition, security perception was found to have a strong effect on trust. Trust is ranked as the third most critical factor affecting behaviour intention after performance expectance and habit. The results make a significant contribution to academic research and have practical implications regarding understanding the role of security in e-government adoption and the factors that affect end users' perception in e-government security.